Polymer Gels : Synthesis and Characterization - Thakur, Vijay Kumar, 1981-, editor 637030; Thakur, Manju Kumari, editor 637031 (Singapore : Springer, 2018)
This book addresses a range of synthesis and characterization techniques that are critical for tailoring and broadening the various aspects of polymer gels, as well as the numerous advantages that polymer gel-based materials offer. It presents a comprehensive collection of chapters on the recent advances and developments in the science and fundamentals of both synthetic and natural polymer-based gels. Topics covered include: synthesis and structure of physically/chemically cross-linked polymer-gels/polymeric nanogels; gel formation through non-covalent cross-linking; molecular design and characterization; polysaccharide-based polymer gels: synthesis, characterization, and properties; modified polysaccharide gels: silica-based polymeric gels as platforms for the delivery of pharmaceuticals; gel-based approaches in genomic and proteomic sciences; emulgels in drug delivery; and organogels. The book provides a cutting-edge resource for researchers and scientists working in various fields involving polymers, biomaterials, bio-nanotechnology and functional materials.